Immunogenicity of recombinant VP2 proteins of all nine serotypes of African horse sickness virus - Kanai, Yuta (Elsevier Science, 2014)
African horse sickness (AHS) is an equine disease with a mortality of up to 90% for susceptible horses. The causative agent AHS virus (AHSV) is transmitted by species of Culicoides. AHSV serogroup within the genus Orbivirus of the Reoviridae family consists of nine serotypes that show no or very limited cross-neutralization. Of the seven structural proteins (VP1-VP7) of AHSV, VP2 is the serotype specific protein, and the major target for neutralizing antibodies. In this report, recombinant VP2 proteins of all nine serotypes were expressed individually by the baculovirus expression system and the immunogenicity of each was studied by immunization of guinea pigs with single VP2 as well as with cocktails of VP2 proteins. Homologous neutralizing antibodies measured by 50% plaque reduction assay showed varying degrees (from 37 to 1365) of titers for different VP2 proteins. A low cross-neutralizing antibody titer was found for genetically related AHSV serotypes. Immunization with VP2 cocktails containing equal amounts of each of the VP2 proteins also triggered neutralizing antibodies albeit to lower titers (4-117) to each of the serotypes in the cocktail. This study is a first step to develop a VP2 subunit vaccine for AHS and our results indicate that VP2 subunit vaccines are feasible individually or in a multi-serotype cocktail.